Associations of fish oil supplementation with incident dementia: Evidence from the UK Biobank cohort study - Huang, Yan; Deng, Yajuan; Zhang, Peizhen; Lin, Jiayang; Guo, Dan; Yang, Linjie; Liu, Deying; Xu, Bingyan; Huang, Chensihan; Zhang, Huijie (Frontiers in Neuroscience, 2022)
Abstract Background: Although numerous studies have investigated the association of dietary intake of omega-3 fatty acids with cognitive function and the risks of dementia, the relationship between fish oil supplementation and incident dementia in a large population-based cohort study has not yet well studied. Methods: A total of 211 094 community-dwelling older persons over 60 years from the UK Biobank cohorts enrolled between 2006 and 2010 that reported regularly taking fish oil and had no dementia at baseline, was included in the present study. All participants completed an electronic questionnaire regarding habitual use of supplements including fish oil. Results: Overall, 83 283 (39.5%) participants reported regularly taking fish oil at baseline. Of 211 094 participants with the median age was 64.1 years, 5 274 participants developed dementia events during a median follow-up of 11.7 years, with 3 290 individuals derived from fish oil non-users. In the multivariable adjusted models, the adjusted hazard ratios (HR) associated with fish oil supplementation for all-cause dementia, vascular dementia, frontotemporal dementia and other dementia were 0.91 [CI, 0.84 to 0.97], 0.83 [CI, 0.71 to 0.97], 0.43 [CI, 0.26 to 0.72], 0.90 [CI, 0.82 to 0.98]), respectively (all P< 0.05). However, no significant association between fish oil supplementation and Alzheimer’s disease was found (HR, 1.00 [CI, 0.89 to 1.12], P= 0.977). In the subgroup analyses, the associations between use of fish oil and the risk of all-cause dementia (P for interaction=0.007,) and vascular dementia were stronger among men (P for interaction=0.026). Conclusions: Among older adults, regular fish oil supplementation was significantly associated with a lower risks of incident all-cause dementia, as well as vascular dementia, frontotemporal dementia and other dementia but not Alzheimer’s disease. These findings support that habitual use of fish oils is beneficial for the prevention of dementia in clinical practice.